2021
DOI: 10.1097/mpg.0000000000003368
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Outcomes in Children With Conditions Affecting the Small Intestine

Abstract: Objectives: The aim of the study was to assess cognitive outcomes in children with intestinal failure (IF) and children at high risk of IF with conditions affecting the small intestine requiring parenteral nutrition. Methods: EMBASE, Cochrane, Web of Science, Google Scholar, MEDLINE, and PsycINFO were searched from inception to October 2020. Studies were included constituting original data on developmental quotient (DQ), intelligence quotient (IQ) and/or severe developmental delay/disability (SDD) rates assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Notably, NEC is not solely a disease of the abdomen, rather it is a multisystemic disease that can also affect other organ systems ( 17 19 ). Systemic reviews have demonstrated that NEC is an independent risk factor for neurocognitive developmental delay and poor neurocognitive outcomes ( 20 , 21 ). Moreover, studies suggest that common morbidities of the preterm infant such as bronchopulmonary dysplasia (BPD) and brain damage are affected by the development of NEC necrotizing enterocolitis, through interactions known as the “Gut-Lung-Axis” and “Gut-Brain-Axis”, respectively ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, NEC is not solely a disease of the abdomen, rather it is a multisystemic disease that can also affect other organ systems ( 17 19 ). Systemic reviews have demonstrated that NEC is an independent risk factor for neurocognitive developmental delay and poor neurocognitive outcomes ( 20 , 21 ). Moreover, studies suggest that common morbidities of the preterm infant such as bronchopulmonary dysplasia (BPD) and brain damage are affected by the development of NEC necrotizing enterocolitis, through interactions known as the “Gut-Lung-Axis” and “Gut-Brain-Axis”, respectively ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the IF population grows older, new challenges concerning long‐term neurodevelopmental outcomes and psychosocial functioning have gained attention. Low gestational age, long hospitalization, and multiple surgical procedures are associated with impaired neurodevelopment in IF (4). There are few published studies concerning the psychological impact of home PN on children with IF and their families (5–9).…”
mentioning
confidence: 99%